GEOGRAPHY IN SONG OF A PEOPLE FROM ONE PLACE - Farias Silva, Elisabete de Fatima [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
From the Humanistic Geography and Phenomenology will discuss her experience motivated by Song of a people from one place music of Caetano Veloso with students of the 6th year of elementary school in studies of apparent movement of the sun. The methodology adopted aimed at exploring the relationship Geography-Music, and from her and with her, instigating the process of learning about geographic phenomena. The music is by, for, with and about people in this sense the work in the classroom with music is intended to encompass these symbolisms and relationships, taking it in its entirety. A thinking and acting nonstop and sharply defined boundaries between walls and government brochures, between individual and collective opposition.
Keywords: Teaching Geography; music; Phenomenology